Housing Price and Household Debt Interactions in Sweden - Turk, Rima (IMF Working Papers; Working Paper ;, 2015)
Sweden is experiencing double-digit housing price gains alongside rising household debt. A common interpretation is that mortgage lending boosted by expansionary monetary policy is driving up house prices. But theory suggests the value of housing collateral is also important for household's capacity to borrow. This paper examines the interactions between housing prices and household debt using a three-equation model, finding that household borrowing impacts housing prices in the short-run, but the price of housing is the main driver of the secular trend in household debt over the long-run. Both housing prices and household debt are estimated to be moderately above their long-run equilibrium levels, but the adjustment toward equilibrium is not found to be rapid. Whereas low interest rates have contributed to the recent surge in housing prices, growth in incomes and financial assets play a larger role. Policy experiments suggest that a gradual phasing out of mortgage interest deductibility is likely to have a manageable effect on housing prices and household debt.